The mutational spectrum of NRAS gene discovers a novel frameshift mutation (E49R) in Saudi colorectal cancer patients - Mahmood Rasool; Absarul Haque; Mohammed Alharthi; Abdulrahman Sibiany; Mohammed Saad Alamri; Samer Mohammed Hassan Alqarni; Irfan A. Rather; Adeel G. Chaudhary; Sajjad Karim; Peter Natesan Pushparaj (Cancer Cell International)
Abstract Colorectal cancer (CRC) is a major health problem the world face currently and one of the leading causes of death worldwide. CRC is genetically heterogeneous and multiple genetic aberrations may appear on course of the disease throughout patient’s lifetime. Genetic biomarkers such as BRAF, KRAS, and NRAS may provide early precision treatment options that are crucial for patient survival and well-being. The aim of this study was to identify pathogenic mutations in the NRAS gene causing colorectal cancer in the Saudi population. We enrolled 80 CRC tumor tissue samples and performed molecular analyses to establish the mutation spectrum status in the western region of Saudi Arabia. We identified 5 different mutations in 10 patients, 4 of whom were reported previously (G10R, E37K, Q61K, and Q61*) in the literature while we discovered one novel lethal insertion mutation (E49R). A novel identified insertion mutation was present in the third codon of the NRAS gene [c.145 insA (p.Glu49ArgTer85)], causing a frameshift in the amino acid sequence of the protein, and leading to an aberrant and truncated protein of 85 amino acids. Subsequent bioinformatics analysis showed that the mutation was highly deleterious and affected protein function to a greater extent. This identification may further improve the prognosis of CRC and benefit subsequent treatment choices.